2017
DOI: 10.1016/j.expneurol.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Strength of cholinergic tone dictates the polarity of dopamine D2 receptor modulation of striatal cholinergic interneuron excitability in DYT1 dystonia

Abstract: Balance between cholinergic and dopaminergic signaling is central to striatal control of movement and cognition. In dystonia, a common disorder of movement, anticholinergic therapy is often beneficial. This observation suggests there is a pathological increase in cholinergic tone, yet direct confirmation is lacking. In DYT1, an early-onset genetic form of dystonia caused by a mutation in the protein torsinA (TorA), the suspected heightened cholinergic tone is commonly attributed to faulty dopamine D2 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 54 publications
11
76
2
Order By: Relevance
“…TorsinB overexpression did not change cortical thickness, striatal volume, striatal Nissl+ small and medium cell number, or striatal GFAP immunoreactivity in Dlx-CKO and Cre control mice ( Figure S6A-D). TorsinB overexpression completely prevented the loss of dorsal striatal ChIs that have been linked to motor and electrophysiologic abnormalities in dystonia mouse models [23,[29][30][31][32][33][34]. Analysis using unbiased stereology demonstrated that Dlx-CKO mice had 33.5% fewer ChIs compared to Cre controls, whereas the B-OE allele completely prevented this loss ( Figure 4C-D).…”
Section: Torsinb Overexpression Prevents Chi Degeneration and Dystonimentioning
confidence: 93%
See 1 more Smart Citation
“…TorsinB overexpression did not change cortical thickness, striatal volume, striatal Nissl+ small and medium cell number, or striatal GFAP immunoreactivity in Dlx-CKO and Cre control mice ( Figure S6A-D). TorsinB overexpression completely prevented the loss of dorsal striatal ChIs that have been linked to motor and electrophysiologic abnormalities in dystonia mouse models [23,[29][30][31][32][33][34]. Analysis using unbiased stereology demonstrated that Dlx-CKO mice had 33.5% fewer ChIs compared to Cre controls, whereas the B-OE allele completely prevented this loss ( Figure 4C-D).…”
Section: Torsinb Overexpression Prevents Chi Degeneration and Dystonimentioning
confidence: 93%
“…These mutants develop abnormal limb and trunk twisting movements as juveniles that are responsive to anti-muscarinic drugs, mimicking key features of the human phenotype. Coincident with the emergence of these movements, these animals exhibit a highly selective loss of dorsal striatal cholinergic interneurons (ChIs), cells that have been implicated in dystonia pathophysiology in electrophysiological studies [29][30][31]. The disease relevant time course of motor features, clear endpoints, and predictive validity of this model provides a critical system for evaluating the effects of torsinB overexpression in a torsinA LOF pathophysiological in vivo setting.…”
Section: Torsinb Overexpression Prevents Chi Degeneration and Dystonimentioning
confidence: 99%
“…The natural signaling bias of the calcium-sensing receptor is also altered in disease states (for review, see Leach et al, 2015). Models of dystonia (a common movement disorder) involving mutation of the protein torsinA demonstrate a pathologic increase in cholinergic tone to affect dopamine interneurons, and there is a change in dopamine signaling polarity and a bias introduced into dopamine signaling from primarily G i/o to noncanonical b-arrestin signaling (Scarduzio et al, 2017). In general, biased signaling is an obvious mechanism to exploit for drug therapy and the existing data with characterized biased ligands certainly show different phenotypical signaling profiles in vivo.…”
Section: Biased Receptor Signalingmentioning
confidence: 99%
“…Impairment of striatal ChIs is central in the production of movement disorders (Pisani et al., ); altered cholinergic signaling is seen in a diverse class of syndromes that include Parkinson's disease (PD; Brichta et al., ; Kalia et al., ; Ztaou et al., ), dystonia (Peterson et al., ; Eskow Jaunarajs et al., ; Scarduzio et al., ), Tourette's syndrome (Xu et al., ; Albin et al., ), and Huntington's disease (Di Filippo et al., ).…”
Section: Movement Disorders Related To Cholinergic Interneuronsmentioning
confidence: 99%